The European Alpha-1 Research Collaboration (EARCO): a new ERS Clinical Research Collaboration to promote research in alpha-1 antitrypsin deficiency. Issue 2 (14th February 2019) - Miravitlles, Marc; Chorostowska-Wynimko, Joanna; Ferrarotti, Ilaria; McElvaney, Noel G.; O'Hara, Karen; Stolk, Jan; Stockley, Robert A.; Turner, Alice; Wilkens, Marion; Greulich, Timm
Alpha-1 antitrypsin deficiency (AATD) is a common but under-recognised genetic condition that affects approximately 1 in 2000 to 1 in 5000 individuals and predisposes to early-onset emphysema and liver disease [1]. Alpha-1 antitrypsin (AAT) is mainly produced in the liver, and its main function is to protect the lung against proteolytic damage, especially from neutrophil elastase [2]. To date, more than 100 variant alleles of the AAT gene ( SERPINA1 ) have been described, but the Z allele is the most prevalent and responsible for severe AATD leading to lung and liver disease [3]. The European Alpha-1 Research Collaboration (EARCO) will promote international research in alpha-1 antitrypsin deficiency http://ow.ly/DWwg30nwCj4